Examination of the Composition of the Luminal Fluid in the Small Intestine of Broilers and Absorption of Amino Acids under Various Ambient Temperatures Measured In vivo - Lemme, A.; Mitchell, M.A. (International Journal of Poultry Science, 2008)
Composition and normal concentrations of nutrients (glucose, methionine, sodium and potassium) as well as the pH and osmolarity were determined in digesta collected from different segments of the small intestine of broilers both under thermoneutral and heat stress conditions in order to formulate a perfusate closely simulating physiologically normal conditions of the small intestine. Whilst glucose and methionine levels of the luminal fluid decreased with passage (p